The evolution of the human foot. Issue 5 (22nd September 2018) - McNutt, Ellison J.; Zipfel, Bernhard; DeSilva, Jeremy M.
Abstract: There are 26 bones in each foot (52 in total), meaning that roughly a quarter of the human skeleton consists of foot bones. Yet, early hominin foot fossils are frustratingly rare, making it quite difficult to reconstruct the evolutionary history of the human foot. Despite the continued paucity of hominid or hominin foot fossils from the late Miocene and early Pliocene, the last decade has witnessed the discovery of an extraordinary number of early hominin foot bones, inviting a reassessment of how the human foot evolved, and providing fresh new evidence for locomotor diversity throughout hominin evolution. Here, we provide a review of our current understanding of the evolutionary history of the hominin foot.